Sacred founders : women, men, and gods in the discourse of imperial founding, Rome through early Byzantine - Angelova, Diliana, 1968- (University of California Press, 2014)
"Sacred Founders argues that from the time of Augustus through early Byzantium, a discourse of imperial founding helped articulate and legitimate imperial authority. Artwork, literature, imperial honors, and the built environment comprised the statements in this multi-authored, empire-wide discourse. These statements were bound by the idea that imperial men and women were sacred founders of the land, mirror images of the empire's divine founders. By establishing a new capital for the Roman Empire, Constantine and his formidable mother, Helena, initiated its Christian transformation. Over time this transformation empowered imperial women, transformed the cult of the Virgin Mary, fueled contests between church and state, and provoked an arresting synthesis of imperial and Christian art. With balanced analysis, Angelova presents a fresh argument about the symbolic logic of Roman rule and uncovers forgotten legacies that profoundly shaped the Christian era"--Provided by publisher.